Online Optical Tomography System for Detecting and Measuring the Diameters of Solid and Transparent Objects - Jamaludin J.; Rahim, RA (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
IEEE Sensors Journal ( Volume: 16, Issue: 16, August 2016)